Development of Animal Development Practicum Guide Based on Science Process Skills Embryogenesis Observation Material - Annisa Rahma Dieni Chaniago; Winda Dwi Kartika; Jodion Siburian (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2023)
This development research aims to develop practical guidelines for animal development based on science process skills on embryogenesis observation material. This study uses a 4D development model which is carried out in 4 stages, namely: 1) the define stage defines the product requirements to be developed. 2) the design stage (design) designing prototypes and storyboards on the guide. 3) the development stage is realizing the storyboard then validating the feasibility of the product which is carried out by material experts and media experts. 4) the dissemination stage was only carried out in a large group trial. Trials were conducted to find out student responses to the guidelines developed, trials were conducted on 92 students who contracted animal development courses. Based on the data analysis, it was obtained that the average material validation was 86.03%, and the media validation was 95.72%, the average percentage of student responses was 85.23%, so it can be concluded that the practicum guide is feasible to use..